2016
DOI: 10.1128/aem.02803-15
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Plasminogen Activator Coating on Implant Surfaces Reduces Staphylococcus aureus Biofilm Formation

Abstract: cStaphylococcus aureus biofilm infections of indwelling medical devices are a major medical challenge because of their high prevalence and antibiotic resistance. As fibrin plays an important role in S. aureus biofilm formation, we hypothesize that coating of the implant surface with fibrinolytic agents can be used as a new method of antibiofilm prophylaxis. The effect of tissue plasminogen activator (tPA) coating on S. aureus biofilm formation was tested with in vitro microplate biofilm assays and an in vivo m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Fibrin-mediated biofilms can be eradicated by plasmin and other fibrinolytic enzymes such as nattokinase or serrapeptase [ 20 ]. Kwiecisnki et al demonstrated that increasing levels of staphylokinase, which activates plasminogen, inhibited biofilm in a mouse catheter infection model [ 32 ], whereas pre-coating catheter surfaces with tissue plasminogen activator also inhibited adhesion and biomass accumulation in the same in vivo model [ 33 ]. The drug dabigatran (a pharmacological inhibitor of both staphylothrombin and thrombin) inhibited fibrin-mediated biofilm by blocking the interaction between Coa/vWbp and prothrombin both in vitro and in a murine central venous catheter model [ 23 ].…”
Section: What Are the Implications Of These Different Biofilm Mechanimentioning
confidence: 99%
“…Fibrin-mediated biofilms can be eradicated by plasmin and other fibrinolytic enzymes such as nattokinase or serrapeptase [ 20 ]. Kwiecisnki et al demonstrated that increasing levels of staphylokinase, which activates plasminogen, inhibited biofilm in a mouse catheter infection model [ 32 ], whereas pre-coating catheter surfaces with tissue plasminogen activator also inhibited adhesion and biomass accumulation in the same in vivo model [ 33 ]. The drug dabigatran (a pharmacological inhibitor of both staphylothrombin and thrombin) inhibited fibrin-mediated biofilm by blocking the interaction between Coa/vWbp and prothrombin both in vitro and in a murine central venous catheter model [ 23 ].…”
Section: What Are the Implications Of These Different Biofilm Mechanimentioning
confidence: 99%
“…This was shown by preventing S. aureus -mediated coagulation by adding a thrombin inhibitor to jugular vein catheters in mice [ 34 ], or by adding human plasminogen to a staphylokinase-overexpressing S. aureus strain, which led to fibrin dissolution as a result of staphylokinase-mediated activation of plasminogen [ 20 ]. Biofilm formation was also reduced by coating implant surfaces with the human tissue plasminogen activator (tPA), and the biofilms that did form were more susceptible to antibiotics [ 35 ]. These are encouraging results for the possibility of preventing biofilm formation to avoid acute infections on new implants.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of S. aureus biofilm infection, some models utilize a large infectious inoculum or introduce implants that are precoated with bacteria (30)(31)(32)(33)(34)(35)(36). A high-challenge dose, particularly in a confined space such as the joint/bone, would be predicted to elicit a vigorous proinflammatory cascade that could likely alter the course of the resultant immune response and bacterial survival.…”
mentioning
confidence: 99%